Corporate Governance and the Information Content of Earnings Announcements: A Cross‐Country Analysis - Lau, Sie Ting; Shrestha, Keshab; Yu, Jing (Contemporary Accounting Research, 2016)
Abstract Using firm‐level data from 23 developed markets, we document a positive association between overall firm‐level governance quality and the informativeness of earnings announcements measured by abnormal stock return variance. This finding is robust after controlling for the potential endogeneity of firm‐level corporate governance. Further analyses reveal that firms with strong governance show little evidence of earnings management, appoint Big 4 auditing firms, and attract analyst following, implying a positive link between strong corporate governance and the information quality of earnings announcements. Finally, there is some evidence that the relation between firm‐level governance and market reactions around the announcements exists only in countries characterized by a transparent information environment and strong legal investor protection.